Respiratory system impedance in different decubitus evaluated by impulse oscillometry in individuals with obesity - Holtz, Mayara; Perossi, Larissa; Perossi, Jéssica; Oliveira dos Santos, Daniele; de Souza, Hugo Celso Dutra; Gastaldi, Ada Clarice (PloS one, 2023)
The body posture can influence gas exchange, respiratory mechanics, and mucociliary clearance and different positions can be used as a therapeutic strategy to improve in gas exchange and can also help physiotherapists to assist patients who have difficult or restrictions to stay seated or the ones who stay in the same position for a long period. The objective of this study was to evaluate the effect of different positions on respiratory system impedance in obese and eutrophic subjects, using Impulse Oscillometry System (IOS). The IOS parameters were evaluated in seated (Se), right lateral decubitus (RL), left lateral decubitus (LL), and supine (Su). Sixty two volunteers were allocated in obese group (OG) or eutrophic group (EG) according to BMI. In seated position, OG showed higher impedance than EG for R5: 0.55 (0.31; 0.93) and 0.33 (0.24; 0.52); R20: 0.39 (0.23; 0.54) and 0.32 (0.03; 0.41); R5-R20: 0.13 (0.02; 0.47) and 0.01 (-0.08; 0.27); X5: -0.20 (-0.51; 0.16) and -0,10 (-0.016; -0.04); Fres: 20.59 (11.54; 36.45 and 10.69 (7.56; 24.7) (p<0.05) and the impedance were higher in the Su for both groups. Compared to Se, there were differences with Su (R5, R5-20, X5), with RL (R20), and with LL (R5, R20) for OG; and with Su (R5, R5-20, X5, Fres), with RL and LL (X5) for EG. Compared to Su, there were differences with RL and LL (R5-20, X5) for OG; and with RL (R5, R5-20, X5, Fres), and LL (R5-20, X5, Fres) for EG. There were no differences between RL and LL for OG and EG. The respiratory system impedance is increased in OG, with greater contribution of peripheral resistance. The higher values of resistance and reactance were obtained in the supine position, in both groups, with lower differences obtained in the right and left lateral decubitus.